Reflections and Future Directions for the Green Maritime Supply Chain in Malaysia - Muhamad Fairuz, Ahmad Jasmi; Fernando, Yudi; Rusdi, Omar; Muhammad Shabir, Shaharudin (IGI Publisher, 2022)
The maritime sector and shipping industry have been argued to be effective drivers of international trade. Internationalization has become a strategic business plan by entrepreneurs and industry players to expand the business, especially when their business was already established in the domestic market. However, current international laws began to be tightened by requiring each exporting and shipping firms to implement green sea transport practices and documentations. A limited number of empirical-based evidence has forced the maritime practitioners to conduct business without clear green concepts knowledge and availability of best business practices to be benchmarked. With this in mind, the aim of this chapter is to examine current issues, differences, and dilemmas confronting practitioners, governments, stakeholders, and scholars. This chapter has developed a green maritime supply chain concept based on practitioners' reflections and provides future direction to scholars interested in studying green logistics and supplying chain management in the maritime sector.